Madrasah diniyah teachers' perceptions on the tajwid recitation program's implementation: A post-training qualitative study - Yusuf Hanafi; Faris Khoirul Anam; Muhammad Saefi; M. Alifudin Ikhsan; Tsania Nur Diyana (Journal of Community Service and Empowerment, 2023)
Formative assessment is often neglected in learning. This study investigates the perception of madrasah diniyah teachers on the planned implementation of the recitation program as part of a formative evaluation in the form of feedback. Twenty madrasah diniyah teachers were asked to respond to a questionnaire that covered three aspects, namely planning, learning outcomes, and teacher support in the post-training. The findings show that teachers have an open view of the implementation of recitation and believe that it can provide significant benefits for student learning outcomes. This paper provides empirical insight into teacher perceptions and provides suggestions for expanding teacher understanding and competence in utilizing recitation programs as an integral element of recitation learning methods and evaluations.